Successful endoscopic treatment of diverticular disease complicated by paracolic abscess - A. I. Khripun; G. B. Makhuova; A. A. Izvekov; M. V. Monakhov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of clinical case presentation. To evaluate potential of intraluminal endoscopy for the treatment of diverticulitis, complicated by paracolic abscess. Summary. The clinical case of complicated colonic diverticula treatment by intraluminal endoscopy is presented. Patient at urgent admission was diagnosed to have “strangulated postoperative ventral hernia”; however the complex laboratory and instrumental investigations revealed inflammatory infiltrate in the right iliac area with signs of abscess formation. Attempts to carry out abscess drainage under ultrasound control were unsuccessful. To rule out potential neoplastic disease and determine the scope of surgical intervention videoassisted colonoscopy was carried out that revealed ascending colon diverticulum as a cause for paracolic abscess. Results. Endoscopic procedure provided successful surgical intervention that resulted in adequate internal drainage of the abscess was subsequent resolution of inflammatory infiltrate and complete patient recovery. Conclusion. Internal endoscopic drainage of the paracolic abscess that developed on the background of colonic diverticulitis can be successful alternative to urgent surgery due to reduction of treatment cost and improvement of quality of life of patients.